Pengetahuan Buruk dan Sikap Negatif Remaja Sejalan dengan Kejadian Kehamilan Tidak Diingingkan - casman, casman (Jurnal Kesehatan Holistic, 2019)
Unwanted pregnancy still became big problem the world. Unwanted pregnancy mostly happen in adolescents, because emotional and physical instability of teenagers makes risk of having an abortion increased, and is influenced by adolescents' knowledge and attitudes. This study aims to determine the relationship between knowledge and attitudes of adolescents with KTD. This study was cross sectional method using the total sample. The results showed that adolescent knowledge and attitudes were not significantly associated with KTD (p> 0.05). KTD is not related to the knowledge and attitudes of adolescents, but one respondent who has KTD is a teenager with less knowledge and negative attitude, so further research is needed, increasing the number of samples and analyzing KTD factors in adolescents.